Selective binding of activated pp60c-src by an immobilized synthetic phosphopeptide modeled on the carboxyl terminus of pp60c-src. - Roussel, R R (1991)
Phosphorylation of the carboxyl terminus of pp60c-src, the product of the c-src protooncogene, at Tyr-527 suppresses its tyrosine kinase activity and transforming potential. It has been proposed that the phosphorylated carboxyl terminus of pp60c-src inhibits kinase activity by binding to the SH2 (src homology 2) domain. We have synthesized peptides corresponding to the carboxyl-terminal 13 residues of pp60c-src phosphorylated and nonphosphorylated at Tyr-527. A highly transforming mutant, pp60c-src(F527), in which Tyr-527 is mutated to Phe, bound to the phosphorylated peptide immobilized to Affi-Gel 10. Binding of the phosphorylated peptide was abolished by deletion of residues 144-175 in the SH2 domain but not by deletion of residues 93-143, which removes most of the SH3 domain. The phosphorylated peptide also bound to pp60v-src, the transforming protein of Rous sarcoma virus. Only traces of pp60v-src and pp60c-src(F527) bound to the corresponding nonphosphorylated c-src peptide. Normal pp60c-src bound much less efficiently to the phosphorylated peptide than did pp60c-src(F527). A phosphorylated peptide corresponding to the carboxyl terminus of the c-fgr protein also bound to pp60c-src(F527), but with weaker affinity. Furthermore, the phosphorylated synthetic carboxyl-terminal pp60c-src peptide markedly inhibited phosphorylation of pp60c-src(F527) during cytoskeletal kinase assays. These results provide direct evidence for models in which the phosphorylated carboxyl terminus of pp60c-src binds intramolecularly or intermolecularly to the SH2 domain of the c-src protein.